ChemInform Abstract: Solid‐Phase Organic Synthesis and Catalysis: Some Recent Strategies Using Alumina, Silica, and Polyionic Resins. Issue 8 (February 2015) - Basu, Basudeb; Paul, Susmita
Abstract Review: 264 refs.